Dietary Supplementation of Spirulina platensis as a Substitute for Antibiotics in Arab Chicken (Gallus turcicus) - Hasna, N. A.; Widiastuti, E.; Agusetyaningsih, I.; Wulandari, E. C.; Murwani, R.; Yudiarti, T.; Sartono, T. A.; Sugiharto, S.; Wahyuni, H. I. (Faculty of Animal Science, IPB University, 2024)
This study was conducted to determine the effect of adding Spirulina platensis to replace zinc bacitracin on performance, egg quality, blood profile, total gut bacteria, and liver histopathology of local indigenous Arab chicken (Gallus turcicus). One hundred and eight 28-week-old laying hens were distributed randomly to three treatments: T0 (control diet), T1 (T0 + 1% S. platensis), and T2 (T0 + 0.04% zinc bacitracin). The treatment was applied for 49 days. S. platensis and zinc bacitracin decreased feed intake (p<0.05), but the egg mass had no significant effect; this provides a good improvement in feed conversion ratio (p<0.05). S. platensis helped maintain persistent egg production (p<0.05). S. platensis and zinc bacitracin provided the best results on haugh unit (p<0.05). S. platensis increased the yolk score (p<0.05). Zinc bacitracin decreased erythrocytes (p<0.05) but was not significantly different from S. platensis. S. platensis and zinc bacitracin increased mean corpuscular volume (MCV) (p<0.05). Blood chemical profile and total gut bacteria were not affected by the treatments. S. platensis was the best at maintaining liver’s health (p<0.05). This research concludes that S. platensis can efficiently optimize feed consumption, enhance performance, maintain egg quality, and protect the liver damage of Arab chicken. Therefore, S. platensis could be considered to replace the use of antibiotics.